HRM FUNCTIONS AND ITS EFFECTIVENESS INRAMBAL LIMITED,CHENNAI - Dr.G.Amutha, A.ANANTHARAMASANKAR, E.SANDHIYA, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Human resource management is concerned with people element in management. Sinceevery organization is made up of people, acquiring their services, developing their skillsmotivating to high level of performances and ensuring that continue to maintain theircommitmentstotheorganizationwhichareessentialtoachieveorganizational objectives. This project is meant to know the human resource policies in the organization. The HRpolicies are a tool to achieve employee satisfaction and thus highly motivated employees.ThemainobjectiveofvariousHRpoliciesistoincreaseefficiencybyincreasingmotivationandthus fulfil organizational goals andobjectives. The objective is to provide the reader with a framework of the HR policy manual andthevariousobjectivesthatthedifferentpoliciesaimtoachieve.Themainfocuswasonthemanageriallevelsofemployeesi nRAMBALLIMITED.Theresearcher has concluded that employeemotivationisneededtobebuiltupthroughconstantattemptsoftheorganization.Theorganizationmayadoptvariou s methodsformotivatingtheemployees